Leishmania infantum in the reproductive organs of dogs - Silva, Diogo Tiago Da; Alves, Maria Luana; Spada, Julio Cesar Pereira; Leonel, João Augusto Franco; Benassi, Julia Cristina; Starke-buzetti, Wilma Aparecida [UNESP]; Ferreira, Helena Lage; Keid, Lara Borges; Soares, Rodrigo Martins; Oliveira, Trícia Maria Ferreira De Sousa (Universidade Federal de Santa Maria, 2021)
Leishmania infantum causes canine leishmaniasis. Using parasitological and molecular analyses, we identified L. infantum in the reproductive organs of male and female dogs. Using histochemistry, immunohistochemistry, and PCR, we examined tissue samples from the reproductive organs of 8 male dogs and 16 female dogs diagnosed with leishmaniasis. Despite the absence of macroscopic or microscopic lesions in these organs, we observed L. infantum amastigotes in tissue samples from the testis and the uterus. PCR and sequencing of these tissues revealed sequences that matched 100% with L. infantum DNA available at GenBank. The presence of L. infantum amastigotes and DNA in testicular and uterine tissue samples suggested that these organs can harbor the parasite without associated macroscopic or microscopic lesions, and this can be especially important in the vertical and venereal transmission of leishmaniasis in dogs.

Leishmania infantum é agente etiológico da leishmaniose canina. Por meio de análises parasitológicas e moleculares, a presença do parasita foi investigada em órgãos reprodutivos de cães machos e fêmeas. Amostras de tecidos dos órgãos reprodutivos de 8 cães machos e 16 fêmeas diagnosticados com leishmaniose foram avaliadas por histoquímica, imunohistoquímica e PCR. Apesar de não terem sido observadas lesões macroscópicas ou microscópicas nos órgãos reprodutivos desses cães, formas amastigotas de L. infantum foram observadas em amostras teciduais do testículo e útero. A PCR e o sequenciamento do DNA extraído desses tecidos revelaram sequências 100% idênticas a L. infantum depositadas no GenBank. Nossos resultados sugerem que os testículos e o útero podem abrigar o parasita, sem associação com lesões macroscópicas ou microscópicas, o que pode ter uma grande importância na transmissão venérea e vertical da leishmaniose entre cães.
Leishmania infantum em órgãos reprodutivos de cães
Keywords: histochemical; immunohistochemical; leishmaniasis; testis; uterus; histoquímica; imunohistoquímica; leishmaniose; testículo; útero